Editorial: Prediction of coastal morphological evolution in the context of climate change adaptation and nature-based engineering - Sergio Maldonado; José A. A. Antolinez; Nicholas Dodd; Rodolfo Silva (Frontiers in Marine Science, 2026)

Healing country together: A seagrass restoration case study from Gathaagudu (Shark Bay) - Elizabeth A. Sinclair; John Statton; Rachel Austin; Martin F. Breed; Richard Cross; Alex Dodd; Amrit Kendrick; Siegfried L. Krauss; Bianca McNeair; Nykita McNeair; Sean McNeair; Marika Oakley; et al. (Ocean & Coastal Management, 2024)

Numerical investigation of swash–swash interaction effects on beachface evolution using Nonlinear Shallow Water Equations - Fangfang Zhu; Nicholas Dodd (Advances in Water Resources, 2023)

Whole life cycle environmental impact assessment of buildings: Developing software tool and database support for the EU framework Level(s) - Catherine De Wolf; Mauro Cordella; Nicholas Dodd; Brandon Byers; Shane Donatello (Resources, Conservation and Recycling, 2023)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Green Nourishment: An Innovative Nature-Based Solution for Coastal Erosion - Wen L. Chen; Peter Muller; Robert C. Grabowski; Nicholas Dodd (Frontiers in Marine Science, 2022)
Coastal erosion poses an urgent threat to life and property in low-lying regions. Sand nourishment is increasingly used as a nature-based solution but requires significant natural resources and replenishment over time. In this study, a novel form of nourishment is explored that combines shoreface nourishment and seagrass restoration to mitigate coastal erosion (i.e., green nourishment). Using the coastal morphodynamic model Xbeach, the impact of seagrass planting on wave energy dissipation, sediment erosion and transport, and morphological evolution of a cross-shore profile was studied for mild wave conditions and an intense storm. Model results indicate that a seagrass meadow enhances the wave energy dissipation provided by a shoreface nourishment, and suggests that it may be particularly effective in sediment transport mitigation when implemented in a sheltered nearshore area. The shoreface nourishment reduced the wave height on the seagrass meadow, and reduced the rate of seagrass destruction by deposition or erosion above the grass height after the storm event. Green nourishment also reduced beach foreshore erosion caused by a simulated storm event. An alternative, more cost-effective planting technique using seagrass seeds was explored, which showed similar coastal erosion protection benefits for seagrass transplants. This modeling study found that green nourishment is potentially an effective nature-based solution for coastal erosion and flooding on sandy coasts, and future studies are recommended to evaluate its morphological, ecological and flood risk reduction benefits in the field.

Numerical modelling of intra-wave sediment transport on sandy beaches using a non-hydrostatic, wave-resolving model - Giulia Mancini; Riccardo Briganti; Robert McCall; Nicholas Dodd; Fangfang Zhu (Ocean Dynamics, 2021)
The mutual feedback between the swash zone and the surf zone is known to affect large-scale morphodynamic processes such as breaker bar migration on sandy beaches. To fully resolve this feedback in a process-based manner, the morphodynamics in the swash zone and due to swash-swash interactions must be explicitly solved, e.g., by means of a wave-resolving numerical model. Currently, few existing models are able to fully resolve the complex morphodynamics in the swash zone, and none is practically applicable for engineering purposes. This work aims at improving the numerical modelling of the intra-wave sediment transport on sandy beaches in an open-source wave-resolving hydro-morphodynamic framework (e.g., non-hydrostatic XBeach). A transport equation for the intra-wave suspended sediment concentration, including an erosion and a deposition rate, is newly implemented in the model. Two laboratory experiments involving isolated waves and wave trains are simulated to analyse the performance of the model. Numerical results show overall better performance in simulating single waves rather than wave trains. For the latter, the modelling of the morphodynamic response improves in the swash zone compared with the existing sediment transport modelling approach within non-hydrostatic XBeach, while the need of including additional physical processes to better capture sediment transport and bed evolution in the surf zone is highlighted in the paper.

Experimental Analysis of Wave Overtopping: A New Small Scale Laboratory Dataset for the Assessment of Uncertainty for Smooth Sloped and Vertical Coastal Structures - Hannah E Williams; Riccardo Briganti; Alessandro Romano; Nicholas Dodd (Journal of Marine Science and Engineering, 2019)
Most physical model tests carried out to quantify wave overtopping are conducted using a wave energy spectrum, which is then used to generate a free surface wave time series at the wave paddle. This method means that an infinite number of time series can be generated, but, due to the expense of running physical models, often only a single time series is considered. The aim of this work is to investigate the variation in the main overtopping measures when multiple wave times series generated from the same spectrum are used. Physical model tests in a flume measuring 15 m (length) by 0.23 m (width) with an operating depth up to 0.22 m were carried out using a stochastic approach on two types of structures (a smooth slope and a vertical wall), and a variety of wave conditions. Results show variation of overtopping discharge, computed by normalising the range of the discharges at a certain wave condition with the maximum value of the discharge in the range up to 10 % , when the same wave time series is used, but this range increases to 75 % when different time series are used. This variation is found to be of a similar magnitude to both the one found with similar experiments looking at the phenomena in numerical models, and that specified by the confidence bounds in empirical methods.

An evaluation of Z-transform algorithms for identifying subject-specific abnormalities in neuroimaging data - Andrew R. Mayer; Andrew B. Dodd; Josef M. Ling; Christopher J. Wertz; Nicholas A. Shaff; Edward J. Bedrick; Carlo Viamonte (Brain Imaging and Behavior, 2018)